Prevenção de Ombro Doloroso no Acidente Vascular Cerebral (AVC) [folder] - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This folder addresses one of the most common complications after Stroke: shoulder pain. It explains the most frequent causes, such as muscle weakness, shoulder subluxation, improper positioning, and incorrect handling of the affected limb. It also provides preventive guidance, including correct positioning, safe transfer techniques, and appropriate mobilization. The goal is to reduce pain, prevent further complications, and support functional recovery.
Shoulder pain after Stroke [folder]
Keywords: Fisioterapia; Acidente vascular cerebral; Reabilitação do Acidente Vascular Cerebral; Prevenção Primária; Reabilitação Neurológica; Physical Therapy; Stroke; Stroke Rehabilitation; Primary Prevention; Neurological Rehabilitation; CIENCIAS DA SAUDE